ELEMEN-ELEMEN PEMBENTUK SISTEM KOTA-LAMA KUPANG - Lake, Reginaldo Christophori; Mberu, Yuliana Bhara; Diaz, Avitu (Jurnal Arsitektur Komposisi, 2019)
Abstract: This research focuses on the old city-area of Kupang as a historical area formed based on the typology and morphology of the city of Kupang in the past. In the study of the existence of the city-old Kupang is associated with aspects of the function and development of the city. The problems studied are what physical elements exist in the old city area that needs to be emphasized in order to be able to support the activities and functions of the old city-area of Kupang and its preservation. The purpose of revealing the physical elements of the old city of Kupang is to become a concept or direction for the design of the morphology of the city of Kupang on an ongoing basis. The results of the study indicate that changes in the Kupang city-old region are influenced by the elements forming the urban area that are in line with the socio-cultural and economic development of the community in the region.Keywords: physical elements, morphology, heritage, city of KupangAbstrak: Penelitian ini berfokus pada kawasan kota-lama Kupang sebagai kawasan bersejarah yang terbentuk berdasarkan tipologi dan morfologi kota Kupang tempo dulu. Dalam kajian keberadaan kota-lama Kupang dikaitkan dengan aspek fungsi dan perkembangan kota. Permasalahan yang dikaji adalah apa saja elemen fisik yang terdapat pada kawasan kota-lama yang perlu dipertegas agar mampu mendukung kegiatan dan fungsi kawasan kota-lama Kupang dan pelestariannya. Tujuan dari mengungkapkan elemen fisik dari kota-lama Kupang dijadikan sebuah konsep atau arahan desain morfologi kota Kupang secara berkelanjutan. Hasil penelitian menunjukkan bahwa perubahan pada kawasan kota-lama Kupang dipengaruhi oleh elemen-elemen pembentuk kawasan kota yang sejalan dengan perkembangan sosial budaya dan ekonomi masyarakat dalam kawasan.Kata Kunci: elemen fisik, morfologi, kota-lama, kota Kupang